2019
DOI: 10.1111/pbi.13209
|View full text |Cite
|
Sign up to set email alerts
|

OsNAC2 integrates auxin and cytokinin pathways to modulate rice root development

Abstract: SummaryThe rice root system is important for growth. The crosstalk between auxin and cytokinin mediates root initiation and elongation. However, it remains unclear how the transcriptional network upstream of the auxin and cytokinin signalling pathways determines root development. Here, we observed that the knockdown of OsNAC2, which encodes a NAC transcription factor, increased the primary root length and the number of crown roots. OsNAC2 predominantly expressed in primary root tips, crown roots and lateral ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 62 publications
6
89
0
1
Order By: Relevance
“…Schaller et al (Schaller et al, 2014) listed three possible explanations of differing, positive or negative regulatory roles of CKs in the process of cell division. The first two are the presence of additional specific regulators or other signals, which have also been reported by others (Reid et al, 2016; Mao et al, 2019), and the third possibility is the level of cytokinin activity. Involvement of additional specific regulators in differentiating the regulatory roles of CKs is also plausible in our case.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Schaller et al (Schaller et al, 2014) listed three possible explanations of differing, positive or negative regulatory roles of CKs in the process of cell division. The first two are the presence of additional specific regulators or other signals, which have also been reported by others (Reid et al, 2016; Mao et al, 2019), and the third possibility is the level of cytokinin activity. Involvement of additional specific regulators in differentiating the regulatory roles of CKs is also plausible in our case.…”
Section: Discussionsupporting
confidence: 67%
“…Some CKX genes might be induced by transcription factors (Reid et al, 2016; Mao et al, 2019). An important role of some NAC transcription factors in regulation of TaCKX expression and subsequent organ development has also been documented in our not yet published results.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Mao et al () investigated the role of NAC transcription factors on root development in rice. Using both down‐regulated (RNAi and CRISPR/Cas9 lines) and overexpression of OsNAC2 , they showed that OsNAC2 is a negative regulator of root growth, reducing both crown root number and root length.…”
Section: Ckx Is Associated With Root Growth and Mineral Enrichment Inmentioning
confidence: 99%
“…In such cases, when gain of function of the target genes is required, mutations of the upstream regulators of the target gene could be used. For instance, Mao et al () were able to enhance the OsCKX4 function in rice by down‐regulating its inactivator, NAC29.…”
Section: Future Perspectivementioning
confidence: 99%
“…Mutation in rice genes regulating auxin distribution and signaling such as CROWN-ROOTLESS4/OsGNOM1 (OsCRL4/OsGNOM1) and PINFORMED1 (OsPIN) display defects in CR development (Kitomi et al 2008, Liu et al 2009. Auxin signaling activates expression of TFs, they, in turn, regulate and integrate the signaling pathway during CR organogenesis , Liu et al 2005, Kitomi et al 2011b, Zhao et al 2009, Coudert et al 2015, Zhang et al, 2018, Lavarenne et al, 2019, Neogy et al, 2019Mao et al, 2020). In this study, we have investigated the global gene network operational during CRP specification and differentiation in rice.…”
Section: Introductionmentioning
confidence: 99%